Draft Second Five-Year Plan Bihar Government of Bihar - Planning Commission (Planning Commission, 1955)
Bihar is predominantly an agricultural State and over 86 per cent of the population are dependant on cultivation for their livelihood. The average size of holding being small, cultivation is dependant almost entirely on the use of bullock power. In 1951, the number of cattle in Bihar was found to be 18.5 millions including about 15 million cows and bullocks and 3.3 million buffaloes ; sheep numbered 1 million and goats 5.9 millions. The number of poultry birds was 8.2 millions. There arc three natural divisions in the STATE, namely, North Bihar Plains, South Bihar Plains and the Chota Nagpur Plateau. The quality of cattle is exceedingly poor in the last named region; fairly good breeds are found over parts of South and North Bihar Plains, but the quality is poor in most parts. The average milk production of cows taking the State as a whole comes to 462 lbs. a year and of buffaloes 1,050 lbs. a year, the average for the Chota Nagpur region is much less than this. The average ploughing capacity of bullock is estimated as 7.6 acres per pair for the State as a whole. During the First Five-Year Plan, 13 key village centres covering 52 out, of, a total number of 71,000 inhabitated villages in the State were started in selected areas. Outside such areas, 1,200 bulls were distributed and 147 artificial insemination centres were started for upgrading the cattle. These measures have proved successful to a very large extent, but their total impact on the problem which is of very great magnitude, has necessarily been slight. Apart from some increase , in milk production in the key village areas as a result of upgrading of cattle, some efforts were made also to increase production of milk and to improve the arrangements for distribution in two towns through the organisation, co-operative milk unions and societies.
Government of Bihar
Printed by the Superintendent Government Printing, Bihar, Patna
Keywords: First Five-Year Plan and levels of development in 1955-56; Targets to be achieved in the Second Five Year Plan; The financial aspects; District and local planning; Problems of Co-ordination; Wasteland reclamation; Veterinary and Animal Husbandry; Veterinary; Animal Husbandry